PAI-1 Expression Is Required for HDACi-Induced Proliferative Arrest in ras-Transformed Renal Epithelial Cells - Stephen P. Higgins; Craig E. Higgins; Paul J. Higgins (International Journal of Cell Biology)
Malignant transformation of mammalian cells with ras family oncogenes results in dramatic changes in cellular architecture and growth traits. The generation of flat revertants of v-K-ras-transformed renal cells by exposure to the histone deacetylase inhibitor sodium butyrate (NaB) was previously found to be dependent on transcriptional activation of the PAI-1 (SERPINE1) gene (encoding the type-1 inhibitor of urokinase and tissue-type plasminogen activators). NaB-initiated PAI-1 expression preceded induced cell spreading and entry into G1 arrest. To assess the relevance of PAI-1 induction to growth arrest in this cell system more critically, two complementary approaches were used. The addition of a stable, long half-life, recombinant PAI-1 mutant to PAI-1-deficient v-K-ras-/c-Ha-ras-transformants or to PAI-1 functionally null, NaB-resistant, 4HH cells (engineered by antisense knockdown of PAI-1 mRNA transcripts) resulted in marked cytostasis in the absence of NaB. The transfection of ras-transformed cells with the Rc/CMVPAI expression construct, moreover, significantly elevated constitutive PAI-1 synthesis (10- to 20-fold) with a concomitant reduction in proliferative rate. These data suggest that high-level PAI-1 expression suppresses growth of chronic ras-oncogene transformed cells and is likely a major cytostatic effector of NaB exposure.